Meshfree modelling of magnetotelluric and controlled-source electromagnetic data for conductive earth models with complex geometries - Long, Jianbo (Frontiers in Earth Science, 2024)
Geophysical electromagnetic survey methods are particularly effective in locating conductive mineral deposits or mineralization zones in a mineral resource exploration. The forward modelling of the electromagnetic responses over such targets is a fundamental task in quantitatively interpreting the geophysical data into a geological model. Due to the ubiquitous irregular and complex geometries associated with the mineral rock units, it is critical that the numerical modelling approach being used is able to adequately and efficiently incorporate any necessary geometries of the Earth model. To circumvent the difficulties in representing complex but necessary geometry features in an Earth model for the existing mesh-based numerical modelling approaches (e.g., finite element and finite difference methods), I present a meshfree modelling approach that does not require a mesh to solve the Maxwell's equations. The meshfree approach utilizes a set of unconnected points to represent any geometries in the Earth model, allowing for the maximal flexibility to account for irregular surface geometries and topography. In each meshfree subdomain, radial basis functions are used to construct meshfree function approximation in transforming the differential equations in the modelling problem into linear systems of equations. The method solves the potential function equations of the Maxwell's equations in the modelling. The modelling accuracy using the meshfree method is examined and verified using one magnetotelluric model and two frequency-domain controlled-source models. The magnetotelluric model is the well-known Dublin Test Model 2 in which the spherical geometry of the conductor in the shallow subsurface may pose as a challenge for many numerical modelling methods. The first controlled-source model is a simple half-space model with the electric dipole source for which analytical solutions exist for the modelling responses. The second controlled-source model is the volcanic massive sulphide mineral deposit from Voisey's Bay, Labrador, Canada in which the deposit's surface is highly irregular. For all modellings, the calculated electromagnetic responses are found to agree with other independent numerical solutions and the analytical solutions. The advantages of the meshfree method in discretizing the Earth models with complex geometries in the forward modelling of geophysical electromagnetic data is clearly demonstrated.